2021
DOI: 10.1021/acs.jpcc.1c03647
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance of Sb2Si2Te6 Monolayers

Abstract: Two-dimensional materials have attracted much attention due to their good thermoelectric (TE) performance caused by the unique density of states at the Fermi energy and low lattice thermal conductivity. Inspired by the high TE performance of bulk Sb2Si2Te6, in this work, the electronic transport, thermal transport, and TE properties of Sb2X2Te6 (X = Si, Ge) monolayers were investigated using density functional theory in combination with the semiclassical Boltzmann transport theory. The results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In particular, Kang et al solved the problem of the disagreement between the experimental and calculated thermal conductivities of boron arsenide by using the three- and four-phonon scattering theories. In addition, thermal conductivity is a key factor that determines the thermal transport properties of a material, while most previous studies on 2D thermal materials have only considered three-phonon scattering for their thermal conductivities, which usually leads to overestimation. Recently, Sun et al studied the thermal conductivity of 2D SnSe in the paraelectric phase by using the SCPH theory combined with high order phonon scattering, and they found that the thermal transport properties of such 2D materials can only be correctly described by using the SCPH theory and four-phonon scattering.…”
mentioning
confidence: 99%
“…In particular, Kang et al solved the problem of the disagreement between the experimental and calculated thermal conductivities of boron arsenide by using the three- and four-phonon scattering theories. In addition, thermal conductivity is a key factor that determines the thermal transport properties of a material, while most previous studies on 2D thermal materials have only considered three-phonon scattering for their thermal conductivities, which usually leads to overestimation. Recently, Sun et al studied the thermal conductivity of 2D SnSe in the paraelectric phase by using the SCPH theory combined with high order phonon scattering, and they found that the thermal transport properties of such 2D materials can only be correctly described by using the SCPH theory and four-phonon scattering.…”
mentioning
confidence: 99%
“…Wang et al found that the ZT value of monolayer ZrS 3 (2.44) is higher than that of the bulk ZrS 3 (1.75) at 800 K. Therefore, further investigations on the thermoelectric performance of low-dimensional perovskite systems are expected. In addition, considering only LA phonon scattering using the deformation potential theory, a large number of thermoelectric materials with promising ZT values have been predicted, including a CdS monolayer (0.78 at room temperature), CdSe monolayer (0.5 at room temperature), 2D KAgSe nanosheet (2.08 at 700 K), monolayer penta-silicene (3.4 and 3.0 for P- and N-type at room temperature), Sb 2 Si 2 Te 6 monolayer (4.52 at room temperature for P-type), 2D heterobilayer (1.1 and 0.3 for P- and N-type doping at 300 K), N-type TiS 3 monolayer (3.1 and 0.5 along the Y and X axes), and so forth. Furthermore, the ZT values of KCuTe (2.71 at 700 K) and monolayer HfN 2 (2.28) are predicted using a simpler constant relaxation time approximation.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional (2D) materials have been widely explored as promising thermoelectric material due to their unique electronic, mechanical, and optical properties compared to those of their corresponding bulk counterparts. For example, theoretical work has shown that monolayer HfN 2 , TiS 3 , hole doped pentasilicene and KCuTe exhibit a high ZT of 2.28 (at 300 K), 3.1 (at 300 K), 3.43 (at 300 K), and 2.71 (at 700 K), respectively. In addition, p-doped monolayer Sb 2 Si 2 Te 6 with doping concentration of 1.85 × 10 13 cm –2 has been predicted to possess a high ZT in the range of 4.52 to 9.63 at temperature between 300 and 700 K . Monolayer mechanical strain has been employed to improve the ZT.…”
Section: Introductionmentioning
confidence: 92%
“…For example, theoretical work has shown that monolayer HfN 2 , TiS 3 , hole doped pentasilicene and KCuTe exhibit a high ZT of 2.28 (at 300 K), 3.1 (at 300 K), 3.43 (at 300 K), and 2.71 (at 700 K), respectively. 9−12 In addition, p-doped monolayer Sb 2 Si 2 Te 6 with doping concentration of 1.85 × 10 13 cm −2 has been predicted to possess a high ZT in the range of 4.52 to 9.63 at temperature between 300 and 700 K. 13 Monolayer mechanical strain has been employed to improve the ZT. The electron mobility of monolayer α-Te can be enhanced up to 8000 cm 2 V −1 s −1 under the influence of tensile strain without affecting the thermal conductivity, thus resulting in a high ZT value of 0.94 (at 300 K) and 2.03 (at 700 K).…”
Section: Introductionmentioning
confidence: 97%